Postoperative complications of epidural analgesia at hysterectomy for gynecologic malignancies: an analysis of the National Surgical Quality Improvement Program. Issue 8 (25th May 2020) - Ackroyd, Sarah A; Hernandez, Enrique; Roberts, Maureen E; Chu, Christina; Rubin, Stephen; Mantia-Smaldone, Gina; Houck, Karen
Abstract : Objective: The aim of this study was to identify the rate of 30-day postoperative complications after the use of epidural in women undergoing hysterectomy for gynecologic malignancy. Secondary outcome was the impact of epidural on hospital length of stay. Methods: A retrospective cohort study was conducted using the American College of Surgeons' National Surgical Quality Improvement Program database. This large dataset includes perioperative risk factors and 30-day post-operative outcomes from more than 680 hospitals. Women who underwent abdominal hysterectomy for a gynecologic malignancy from January 2014 to December 2017 were included. Adult patients (18 years or older) who underwent abdominal hysterectomy were identified using common procedure terminology and international classification of diseases codes. Only laparotomy cases were included, and minimally invasive cases (laparoscopy, transvaginal) were excluded due to the small prevalence of epidural cases in this cohort. All patients received general anesthesia. If patients were noted to have "epidural anesthesia" they were included in the epidural cohort and those receiving other adjuvant techniques (regional blocks or spinal anesthesia) were excluded. The primary outcome of interest was the 30-day occurrence of a pulmonary embolism, deep-vein thrombosis, pneumonia, and urinary tract infection. Those who received epidural analgesia were matched in a 1:1 ratio with a similar group of patients who did not receive epidural analgesia using a calculated propensity score to control for confounding factors. Results: A total of 2035 (13.8%) patients undergoing abdominal hysterectomy for a gynecologic malignancy received epidural analgesia. 1:1 propensity-matched samples included 2035 patients in both epidural and no-epidural groups. Patient characteristics between groups were similar. Overall 30-day complication rates were higher in the epidural group (75.9% vs 62.0%, P<0.01). Specific complications that were higher in the epidural group included: blood transfusion (28.9% vs 22.8%); wound disruption (2.0% vs 1.1%); surgical site infection (10.1% vs 7.2%); and delay in return of bowel function (12.3% vs 9.3%) (all P<0.05). Hospital length of stay was significantly longer in the epidural group as compared with the no-epidural group (5.69 days vs 4.79 days, P<0.01) and readmissions were higher in the epidural group (10.5% vs 9.7%, P<0.01), but there was no difference in 30-day mortality between the groups (P=0.62). Discussion: The rate of 30-day complications and length of stay among women undergoing an abdominal hysterectomy for gynecologic malignancy was higher for those who received epidural analgesia, but there was no difference in 30-day mortality. Although epidural analgesia can provide a number of benefits when used for postoperative pain control, the possible association with increased 30-day morbidity and length of stay needs to be considered.